2001
DOI: 10.1182/blood.v98.5.1512
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production by mouse myeloid dendritic cells in relation to differentiation and terminal maturation induced by lipopolysaccharide or CD40 ligation

Abstract: IntroductionMyeloid dendritic cells (DCs) are crucial antigen-presenting cells (APCs) for primary T-cell responses. They arise from bone marrow (BM) precursors that colonize peripheral tissues through the blood or lymph. 1,2 Tissue-resident immature DCs are excellent at internalizing and processing antigen, but they exhibit low ability to stimulate naive T cells. Exposure to allergens, bacterial (lipopolysaccharide [LPS], CpG DNA motifs) or viral (dsRNA) components, proinflammatory cytokines (interleukin-1␤ , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
169
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(188 citation statements)
references
References 71 publications
16
169
1
2
Order By: Relevance
“…Bacterial components (e.g. LPS, lipoteichoic acid) have been shown to induce IL-1 § , IL-6 or TNF- § secretion in human monocyte-derived DC [23][24][25][26], and LPS up-regulates IL-1 § and IL-6 expression in mice [27]. Our results clearly showed that MALP-2-treated DC secrete IL-12, suggesting that the resulting T cell response is directed versus a Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial components (e.g. LPS, lipoteichoic acid) have been shown to induce IL-1 § , IL-6 or TNF- § secretion in human monocyte-derived DC [23][24][25][26], and LPS up-regulates IL-1 § and IL-6 expression in mice [27]. Our results clearly showed that MALP-2-treated DC secrete IL-12, suggesting that the resulting T cell response is directed versus a Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…Maturation can be triggered by multiple stimuli, including contact components of bacteria and viruses, proinflammatory cytokines, and CD40-CD40L signaling. [47][48][49][50] Since Ad contains viral components, we sought to understand what effects Ad-infection would have on the maturation status of DCs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, LPS can induce the production of IL-12 by dendritic cells and provide an important signal for a Th1 shift (40). Alternatively, the lipid A portion of LPS can inhibit IL-4 production by CD4 ϩ T cells without inhibiting the production of IFN-␥ (41).…”
Section: Discussionmentioning
confidence: 99%